The concept of timeless self in the Bernau Manuscripts - Espitia Raba, Miguel Ángel (2024)
From a phenomenological perspective, the function that the timeless self plays in the constitution of the temporal experience of the world according to the Bernau Manuscripts is investigated here. The thesis defended is that the function of the timeless self —abstractly considered— is to be the correlative pole and support of all experience, which is temporalized when it is intertwined with subjective experiences, whether bodily or thoughts carried out by the cogito.